Whole-exome sequencing reveals known and candidate genes for hearing impairment in Mali - Abdoulaye Yalcouyé; Isabelle Schrauwen; Oumou Traoré; Salia Bamba; Elvis Twumasi Aboagye; Anushree Acharya; Thashi Bharadwaj; Rachel Latanich; Kevin Esoh; Cesar A. Fortes-Lima; Carmen de Kock; Mario Jonas; et al. (HGG Advances)
Summary: Hearing impairment (HI) is the most common neurosensory disorder globally and is reported to be more prevalent in low-income countries. In high-income countries, up to 50% of congenital childhood HI is of genetic origin. However, there are limited genetic data on HI from sub-Saharan African populations. In this study, we investigated the genetic causes of HI in the Malian populations, using whole-exome sequencing. Furthermore, cDNA was transfected into HEK293T cells for localization and expression analysis in a candidate gene. Twenty-four multiplex families were enrolled, 50% (12/24) of which are consanguineous. Clustering methods showed patterns of admixture from non-African sources in some Malian populations. Variants were found in six known nonsyndromic HI (NSHI) genes, four genes that can underlie either syndromic HI (SHI) or NSHI, one SHI gene, and one novel candidate HI gene. Overall, 75% of families (18/24) were solved, and 94.4% (17/18) had variants in known HI genes including MYO15A, CDH23, MYO7A, GJB2, SLC26A4, PJVK, OTOGL, TMC1, CIB2, GAS2, PDCH15, and EYA1. A digenic inheritance (CDH23 and PDCH15) was found in one family. Most variants (59.1%, 13/22) in known HI genes were not previously reported or associated with HI. The UBFD1 candidate HI gene, which was identified in one consanguineous family, is expressed in human inner ear organoids. Cell-based experiments in HEK293T showed that mutants UBFD1 had a lower expression, compared to wild type. We report the profile of known genes and the UBFD1 candidate gene for HI in Mali and emphasize the potential of gene discovery in African populations.